Penerapan KYC Melalui CDD dan EDD Dalam Upaya Pencegahan dan Pemberantasan Money Laundering dan Terorisme Pada Pengguna Jasa Keuangan - ONY THOYIB HADI WIJAYA; Kirana Salsabilla Citra Wijaya; Yohanes Jentanu Nelson (STEKOM PRESS, 2024)
This research aims to analyze the implementation of Know Your Customer (KYC) through Customer Due Diligence (CDD) and Enhanced Due Diligence (EDD) in the efforts to prevent and combat money laundering and terrorism within the financial services user base. In this study, the research method employed is literature review. The findings of this research can be utilized to support the development of policies and strategies for the prevention and eradication of money laundering and terrorism within the financial services user community. The application of KYC through CDD and EDD is crucial in reducing malicious risks, preventing theft of funds, and maintaining integrity and transparency in financial transactions. Therefore, it is essential for financial institutions and stakeholders to continuously develop and manage the KYC processes effectively and sustainably.